Gathering scientific evidence for a new bioactive natural ingredient: The combination between chemical profiles and biological activities of Flueggea virosa extracts. (October 2022) - Zengin, Gokhan; Dall'Acqua, Stefano; Sinan, Kouadio Ibrahime; Uba, Abdullahi Ibrahim; Sut, Stefania; Peron, Gregorio; Etienne, Ouattara Katinan; Kumar, Manoj; Cespedes-Acuña, Carlos L.; Alarcon-Enos, Julio; Mollica, Adriano; Mahomoodally, Mohamad Fawzi
Abstract: Flueggea virosa (Roxb. ex Willd.) Royle is a plant with several traditional uses in tropical countries. To study the potential usefulness, extracts from stem barks and leaves of F. virosa were obtained with different solvents. The phytochemical composition was assessed using LC-MS and NMR. Triterpenes, as oleanolic (0.05–88.09 mg/g extract), and ursolic (0.03–94.36 mg/g extract) acids were determined. In addition, ellagic and gallic acid derivatives were present in large concentrations in some of the extracts. Antioxidant (radical scavenging, reduction ability, and metal chelating) and enzyme inhibitory (cholinesterase, tyrosinase, amylase, and glucosidase) effects were assessed by in vitro chemical assays. The methanol extracts and infusions from both parts show higher antioxidant ability when compared with ethyl acetate extracts, and the antioxidant capacity was correlated with the total phenolic contents of the tested extracts. The extracts demonstrate enzyme inhibitory abilities on AChE and BChE, and multivariate approaches allowed for correlating the activities with the presence of triterpenoids (R > 0.8). Furthermore, molecular docking was used to get insights into the interactions between the triterpenoids and the tested enzymes. Together, these results indicate that F. virosa represents a significant source of naturally-occurring bioactive compounds that can be exploited as a new ingredient for the development of novel functional products with promising biological properties.